Transformative Applications of Chatgpt: Transforming the medical sector, the oil industry, financial embezzlement, and digital risk protection - Hussain, Ibrar (CV. Multi Kreasi Media, 2024)
Chatgpt is a novel NLP model currently in the process of revolutionizing numerous industries in delivering effective and revolutionary opportunities for improving productivity, decision-making, and interaction. In healthcare, Chatgpt enhances the patient experience, assists in clarity of diagnosis, streamlines operational duties, and hastens creating groundbreaking medical discoveries thereby enhancing the delivery of healthcare in every aspect. In fraud detection, it improves security systems through the detection of patterns of potential security breaches, compliance and regulation system improvement. Chatgpt is advantageous for the petroleum industry in improving the execution of processes, safety measures and innovations, and generally the drive towards more sustainable endeavors. To summarize, Chatgpt enhances cybersecurity threat identification, automates response to cyber threats, and educates users on Computer systems enhancing an organizations protection against cyber threats. Yet, as we noted, Chatgpt provides a great many benefits and therefore its effective application poses a number of challenges, including data privacy, model accuracy, and ethical issues. If organizations implement Chatgpt into these sectors with proper regulation and the right precautions and supervision from people, organizations will reap the benefits of its result and embark on revolutions in various sectors of industry that are equally important to those sectors. As AI technology deepens, Chatgpt will take more importance in determining the future of technology to industries and make them more flexible, productive, and environment-friendly.